Fevereiro 2024 (Abstracta, 2024)
Artigos publicados 2023 - P322-2023 à P385-2023Eventos publicados 2023 - P386-2023 à P387-2023Meeting abstract 2023 - Me001-2023Artigos publicados 2024 - P001-2024 à P016-2024Defesas de Dissertações do IFGW - D001-2024 à D006-2024Defesas de Teses do IFGW - T001-2024 à T003-2024Defesas do PECIM - P001-2024